Designing a Sustainable Entrepreneurship Skills Development and SMME Growth Model for Zimbabwe: Lessons Learned from Masvingo Province Investigation - SEELETSE, Solly Matshonisa; Jongwe, Pamire; Ndobe, Tsakani Violet; Ladzani, Watson Mmboswobeni (REVENUE: Jurnal Manajemen Bisnis Islam, 2025)
Small, Medium, and Micro Enterprises (SMMEs) are pivotal to Zimbabwe's economic growth. Yet, they face significant challenges, such as limited access to finance, inadequate infrastructure, regulatory barriers, and a lack of entrepreneurial skills. This manuscript presents the design of a sustainable entrepreneurship skills development and SMME growth model referred to as Objectives, Phased Framework, and Enabling Ecosystem (OPFEE)  based on insights from a comprehensive investigation conducted in Masvingo Province. The study highlights the essential elements of fostering a conducive environment for SMME growth, emphasizing the need for practical skills, financial inclusion, infrastructure, and regulatory reform. It outlines a phased approach to support entrepreneurship in Zimbabwe, identifying the critical steps needed to transform SMMEs into key drivers of economic growth.